2016
DOI: 10.18632/oncotarget.10070
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled2 signaling regulates growth of high-risk neuroblastomas by interfering with β-catenin-dependent and β-catenin-independent signaling pathways

Abstract: Frizzled2 (FZD2) is a receptor for Wnts and may activate both canonical and non-canonical Wnt signaling pathways in cancer. However, no studies have reported an association between FZD2 signaling and high-risk NB so far. Here we report that FZD2 signaling pathways are critical to NB growth in MYCN-single copy SK-N-AS and MYCN-amplified SK-N-DZ high-risk NB cells. We demonstrate that stimulation of FZD2 by Wnt3a and Wnt5a regulates β-catenin-dependent and –independent Wnt signaling factors. FZD2 blockade suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
3
27
2
Order By: Relevance
“…In fact, we found that MYCN and MYC protein levels were actually reduced after Wnt3a/Rspo2 treatment, in contrast to previous reports suggesting induction of MYC in non-MYCN amplified (non-MNA) NBs as a result of Wnt/β-catenin signalling (Liu et al 2008). Furthermore, our study did not align simply with reports showing that individual Wnt pathway components were associated with chemoresistance (FZD1) (Flahaut et al 2009), tumorigenic stem-like cells in human and mouse neuroblastoma (FZD6) (Cantilena et al 2011), and increased NB proliferation dependent on FZD2 (Zins et al 2016). Using Wnt chemical agonists and inhibitors another study suggested that Wnt signalling hyperactivation promotes apoptosis of NB cells, and that Wnt inhibition decreased proliferation and increased NB differentiation (Duffy et al 2016).…”
Section: Neuroblastoma and Wnt Signallingcontrasting
confidence: 96%
“…In fact, we found that MYCN and MYC protein levels were actually reduced after Wnt3a/Rspo2 treatment, in contrast to previous reports suggesting induction of MYC in non-MYCN amplified (non-MNA) NBs as a result of Wnt/β-catenin signalling (Liu et al 2008). Furthermore, our study did not align simply with reports showing that individual Wnt pathway components were associated with chemoresistance (FZD1) (Flahaut et al 2009), tumorigenic stem-like cells in human and mouse neuroblastoma (FZD6) (Cantilena et al 2011), and increased NB proliferation dependent on FZD2 (Zins et al 2016). Using Wnt chemical agonists and inhibitors another study suggested that Wnt signalling hyperactivation promotes apoptosis of NB cells, and that Wnt inhibition decreased proliferation and increased NB differentiation (Duffy et al 2016).…”
Section: Neuroblastoma and Wnt Signallingcontrasting
confidence: 96%
“…Examples include high FZD1 expression associated with chemoresistance [21], FZD6 marking highly tumorigenic stem-like cells in mouse and human neuroblastoma [22], and FZD2-dependent proliferation of neuroblastoma lines [23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the role of the Wnt signalling pathway, often clearly oncogenic in both adult and childhood cancers such as colorectal cancer and Wilms' tumour (1), has been found to exert more complex influences in NB, as shown several laboratories, including ours. These data have indicated Wnt-induced growth promotion or suppression (13,16,40,41), modulation of signalling and transcriptional pathways, interactions with MYCN (16,41), and underlying changes in differentiation states contributing to neuroblastoma tumour heterogeneity (16,19). In this study, we define a Wnt-BMP growth inhibitory axis in neuroblastoma, identifying MSX and Notch signalling as downstream mediators of growth suppression.…”
Section: Discussionmentioning
confidence: 87%